The new knitting stitch dictionary : 500 patterns for textures, lace, aran cables, colorwork, motifs, edgings and more /: 500 patterns for textures, lace, aran cables, colorwork, motifs, edgings and more. ([2023]) - Klos, Lydia
No abstract available